Straw pyrolysis reverses forest soil N2O emissions from stimulation to suppression by altering organic C quality and N cycling pathways - Yanfei Dong; Dafeng Hui; Jiashu Zhou; Tida Ge; Junjie Lin; Yu Luo; Yuxue Liu; Bing Yu; Yanjiang Cai; Jason C. White; Yongfu Li (Chemical Engineering Journal, 2026)

Double-edged sword effects of degradable microplastics as carbon-active inputs on soil net carbon balance: A critical perspective - Shuai Zhou; Ruimin Qi; Amit Kumar; Dafeng Hui; Shengdao Shan; Junjie Lin (Biology and Fertility of Soils, 2026)

Optimization of fermentation conditions for recombinant McXyn0243 xylanase from Malbranchea cinnamomea and its application in producing xylooligosaccharides from sugarcane bagasse - Jinghao Ma; Lin Dai; Ruiwen Cheng; Fei Xiao; Yongbo Qu; Jianshan Fu; Jianhui Wen; Rana Abdul Basit; Dafeng Yin; Guangsen Fan (Biocatalysis and Agricultural Biotechnology, 2026)

Contrasting fine root-induced rhizosphere priming effects between coniferous and broadleaved trees - Weijun Zhang; Junjie Lin; Qitai Cheng; Liming Yin; Wenling Zhang; Amit Kumar; Xiali Mao; Hongxin Dong; Dafeng Hui; Mengguang Han; Lei Tao; Dingxin Su; et al. (Biology and Fertility of Soils, 2026)

Electronic reconfiguration enhanced oxidase-mimicking activity of Cu–Mn3O4 for colorimetric detection of total antioxidant capacity - Xiaoliang Li; Zizhong Chen; Chengji Sui; Lin Wang; Fengjia Zheng; Fenghua Li; Xiaoxu Yang; Yanni Jiao; Dafeng Jiang (Analytica Chimica Acta, 2026)

Application of feruloyl esterase BpFae03105 and xylanase XynAS Co-enzymolysis to produce ferulic acid from wheat bran - Han Lichun; Zhong Xiufang; Fu Zhilei; Yan Jinlong; Xiao Lin; Zhu Yuting; Liu Xiaoyan; Rana Abdul Basit; Wang Jinpeng; Yin Dafeng; Fan Guangsen (Biocatalysis and Agricultural Biotechnology, 2025)

Priming effects by cellulose inputs decrease with warming regardless of the decomposition stages of soil carbon pools - Junjie Lin; Guoxin Lan; Zhenyu Yang; Shuang Zhou; Dafeng Hui; Peng Wang; Shuai Zhang; Lifeng Ping; Shengdao Shan (Plant and Soil, 2025)

Effects of soil moisture fluctuation and microplastics types on soil organic matter decomposition and carbon dynamics - Junjie Lin; Beibei Chen; Hongxin Dong; Wenling Zhang; Amit Kumar; Dafeng Hui; Changai Zhang; Shengdao Shan; Biao Zhu (Soil Biology and Biochemistry, 2025)

Drying-rewetting cycles decrease temperature sensitivity of soil organic matter decomposition - Junjie Lin; Wenling Zhang; Amit Kumar; Dafeng Hui; Changai Zhang; Shengdao Shan; Zhiguo Yu; Biao Zhu; Yakov Kuzyakov (Agricultural and Forest Meteorology, 2025)

Determination of arsenic speciation of arsenic in squid and its human consumption risk - Chuan Qin; Yanni Jiao; Luping Yang; Lin Wang; Zhengqiao Kong; Dafeng Jiang; Jiacheng Zhang; Tianliang Zhang; Xibao Gao (Environmental Science and Pollution Research, 2025)

Contrasting effects of litter and root removals on soil N2O emissions of an evergreen broadleaved forest in southeastern China - Lei Zhang; Weisheng Lin; Jordi Sardans; Enlan Xu; Dafeng Hui; Xiaofei Liu; Jinsong Wang; Shidong Chen; Jianfen Guo; Josep Peñuelas; Yusheng Yang (Applied Soil Ecology, 2025)

Optimizing multiple ecosystem services in Eucalyptus plantations: Dual effects of intercropping and restoration - Lei Zhang; Siyu Liu; Yanjia Wang; Fangwei Zhang; Qiuyu Luo; Yongbiao Lin; Dafeng Hui; Shenglei Fu; Jun Wang; Zhanfeng Liu; Ruoyi Lin; Hai Ren; et al. (Journal of Cleaner Production, 2024)

Alterations in leukocyte telomere length and mitochondrial DNA copy number in benzene poisoning patients - Dianpeng Wang; Dafeng Lin; Xiangli Yang; Dongpeng Wu; Peimao Li; Zhimin Zhang; Wen Zhang; Yan Guo; Song Fu; Naixing Zhang (Molecular Biology Reports, 2024)

Sensitive and rapid detection of three foodborne pathogens in meat by recombinase polymerase amplification with lateral flow dipstick (RPA-LFD) - Wenxia Bai; Jie Chen; Dong Chen; Yike Zhu; Kairui Hu; Xiaoyu Lin; Junlin Chen; Dafeng Song (International Journal of Food Microbiology, 2024)

Soil warming-induced reduction in water content enhanced methane uptake at different soil depths in a subtropical forest - Lei Zhang; Weisheng Lin; Jordi Sardans; Xiaoling Li; Dafeng Hui; Zhijie Yang; Haizhen Wang; Hao Lin; Yufang Wang; Jianfen Guo; Josep Peñuelas; Yusheng Yang (Science of The Total Environment, 2024)

Multi‐ecosystem services differently affected by over‐canopy and understory nitrogen additions in a typical subtropical forest - Yang Tian; Peng Zhou; Lang Zhou; Lei Zhang; Yongbiao Lin; Yanjia Wang; Jun Wang; Dafeng Hui; Hai Ren; Hongfang Lu (Global Change Biology, 2024)
Obtaining a holistic understanding of the impacts of atmospheric nitrogen deposition on multiple ecosystem services of forest is essential for developing comprehensive and sustainable strategies, particularly in heavy N deposition regions such as subtropical China. However, such impacts remain incompletely understood, with most previous studies focus on individual ecosystem function or service via understory N addition experiments. To address this knowledge gap, we quantified the effects of over‐canopy and understory N additions on multiple ecosystem services based on a 7‐year large‐scale field experiment in a typical subtropical forest. Our results showed continued over‐canopy N addition with 50 kg ha −1 year −1 over a period of 4–7 years significantly increased plant nutrient retention, but did not affect the services of soil nutrient accumulation, water yield, C sequestration (in plants and soil), or oxygen release. There were trade‐offs between the soil and plant on providing the services of nutrient accumulation/retention and C sequestration under over‐canopy N addition. However, without uptake and retention of tree canopy, the trade‐off between soil and plant were more weaken under the understory N addition with 50 kg ha −1 year −1 , and their relationships were even synergetic under the understory N addition with 25 kg ha −1 year −1 . The results suggest that understory N addition cannot accurately simulate the effects of atmospheric N deposition on multiple services, along with mutual relationships. Interestingly, the services of plant N, P retention, and C sequestration exhibited a synergetic increase under the over‐canopy N addition but a decrease under the understory N addition. Our results also found tree layer plays a primary role in providing plant nutrient retention service and is sensitive to atmospheric N deposition. Further studies are needed to investigate the generalized effects of forest canopy processes on alleviating the threaten of global change factors in different forest ecosystems.

Decreased glomalin-related soil protein with nitrogen deposition in a 3-year-old Cunninghamia lanceolata plantation - Shuxian Jia; Xiaofei Liu; Weisheng Lin; Yong Zheng; Jianwei Li; Dafeng Hui; Jianfen Guo (Journal of Soils and Sediments, 2022)

Air-pollutant mass concentration changes during COVID-19 pandemic in Shanghai, China - Zhi Niu; Tingting Hu; Lin Kong; Wenqi Zhang; Pinhua Rao; Dafeng Ge; Mengge Zhou; Yuseng Duan (Air Quality, Atmosphere & Health, 2021)

Effects of Grazing, Wind Erosion, and Dust Deposition on Plant Community Composition and Structure in a Temperate Steppe - Mengmei Zheng; Jian Song; Jingyi Ru; Zhenxing Zhou; Mingxing Zhong; Lin Jiang; Dafeng Hui; Shiqiang Wan (Ecosystems, 2021)

Joint association of carrying HLA-B*13:01 gene and human herpesvirus-6 with occupational trichloroethylene hypersensitivity syndrome - Dianpeng Wang; Dafeng Lin; Peimao Li; Huimin Liu; Yanhua Yang; Zhimin Zhang; Qiuyue Kong; Yanfang Zhang; Xianqing Huang (International Archives of Occupational and Environmental Health, 2019)

Gao et al. (2016): Change of urinary cadmium and renal tubular protein in female works after cessation of cadmium exposure - Dafeng Lin (International Archives of Occupational and Environmental Health, 2017)

A longitudinal study on urinary cadmium and renal tubular protein excretion of nickel–cadmium battery workers after cessation of cadmium exposure - Yanhua Gao; Yanfang Zhang; Juan Yi; Jinpeng Zhou; Xianqing Huang; Xinshan Shi; Shunhua Xiao; Dafeng Lin (International Archives of Occupational and Environmental Health, 2016)